Assessment of personality-related levels of functioning: a pilot study of clinical assessment of the DSM-5 level of personality functioning based on a semi-structured interview. Issue 1 (December 2016) - Thylstrup, Birgitte; Simonsen, Sebastian; Nemery, Caroline; Simonsen, Erik; Noll, Jane; Myatt, Mikkel; Hesse, Morten
Abstract Background The personality disorder categories in the Diagnostic and Statistical Manual of Mental Disorders IV have been extensively criticized, and there is a growing consensus that personality pathology should be represented dimensionally rather than categorically. The aim of this pilot study was to test the Clinical Assessment of the Level of Personality Functioning Scale, a semi-structured clinical interview, designed to assess the Level of Personality Functioning Scale of the DSM-5 (Section III) by applying strategies similar to what characterizes assessments in clinical practice. Methods The inter-rater reliability of the assessment of the four domains and the total impairment in the Level of Personality Functioning Scale were measured in a patient sample that varied in terms of severity and type of pathology. Ratings were done independently by the interviewer and two experts who watched a videotaped Clinical Assessment of the Level of Personality Functioning Scale interview. Results Inter-rater reliability coefficients varied between domains and were not sufficient for clinical practice, but may support the use of the interview to assess the dimensions of personality functioning for research purposes. Conclusions While designed to measure the Level of Personality Functioning Scale with a high degree of similarity to clinical practice, the Clinical Assessment of the Level of Personality Functioning Scale had weak reliabilities and a rating based on a single interview should not be considered a stand-alone assessment of areas of functioning for a given patient.